Application of E-Glass Jute Hybrid Laminate Composite with Curved Shape on Compressive Strength of Cylindrical Column Concrete - Achmad Jusuf Zulfikar; Mohd Yuhazri Yaakob; Rahmad Bayu Syah (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2023)
This study provides a better understanding of reinforcing cylindrical concrete columns (CCC) using a hybrid laminated composite material (HLC) composed of jute and e-glass fibers, including the influence of layer quantity on strength and a comparison with previous research. The utilization of these alternative materials may lead to the development of novel and efficient solutions for constructing durable and robust structures. The primary objectives of this research are to assess the effects of employing HLC as a reinforcing layer on CCC compressive strength, optimize the reinforcement process by selecting appropriate layer sequences and types, and analyze the type of fiber damage in relation to the strength of HLC composite material. The materials utilized in this study encompass woven jute fabric sheets, e-glass fiber sheets, and epoxy resin. Compressive strength testing was conducted following ASTM C39 standards. Specimen variations were based on the number and type of reinforcing layers. The results revealed that CCC compressive strength increased by up to 100% with the application of up to three layers of jute compared to an unlayered specimen. Furthermore, CCC compressive strength experienced a remarkable enhancement of up to 150% with the incorporation of HLC composite. Hence, the implementation of HLC demonstrates significant potential for augmenting the strength of concrete structures.